A step toward lifting the fog off mist explosions: Comparative study of three fuels. (January 2022) - El – Zahlanieh, Stephanie; Sivabalan, Shyarinya; Dos Santos, Idalba Souza; Tribouilloy, Benoit; Brunello, David; Vignes, Alexis; Dufaud, Olivier
Abstract: Gases, vapors, and dusts are all potential explosion threats; however, mists should also be taken into account. Indeed, dozens of accidents involving hydrocarbon mists were identified in incident surveys. Mist explosions continue to occur, highlighting the need to evaluate and assess the validity of present approaches for assessing mist ATEX risks and to establish reliable standardized safety parameters for fuel mists. In a modified apparatus based on the 20 L explosion sphere, three fluids of industrial interest were investigated. A new siphon injection system comprising a Venturi junction was installed, offering a wide range of dispersion performances. This system was controlled by a specifically developed program, ensuring the apparatus's versatility and adaptability to various tested liquids. It enables precise control of the gas carrier flow, liquid flow, and injection and ignition durations, allowing modification of the dilution rate of a particular droplet size distribution (DSD). The mist cloud dispersed in the 20 L sphere was characterized by determining its DSD using an in-situ laser diffraction sensor and by performing Particle Image Velocimetry (PIV). Mists of kerosene, diesel and ethanol were then subjected to tests to assess their lower explosive limit (LELmist ), minimum ignition energy (MIE), maximum explosion pressure (Pmax ), and rate of pressure rise (dP/dtmax ). For instance, it was found that the LELmist of ethanol, kerosene Jet A1, and diesel fuel for a DSD averaged at 8–10 μm reach 77, 94, and 93 g/m 3 respectively. This LELmist was also shown to increase with increasing DSD in the case of Jet A1 mists. A sensitivity study was also performed to emphasize the impact of parameters such as the fuel type, the DSD, and the mist temperature. Findings showed that the explosion severity is strongly influenced by the chemical nature and the volatility of the dispersed fuel. Moreover, controlling the sphere temperature was proven to be a crucial step when using such apparatus for the evaluation of the explosibility of mists. An evaporation model based on the d 2 law was also developed to visualize the vapor-liquid ratio before ignition. These findings have already led to the development of a new procedure for determining safety standards for hydrocarbon mists, as well as tools to assess mist explosion risks. They have proven that it is possible to evaluate the ignition sensitivity and explosion severity of fuel mists using a single well-known apparatus. Highlights: Hydrocarbon mist explosivity can be assessed using a modified 20 L sphere. Turbulence levels and droplet size distributions (DSD) of mists can be varied. The explosivity and flammability of ethanol, JetA1, and diesel mists were compared. LEL values of fuel mists increase with increasing DSD or decreasing volatility. Increasing temperature or decreasing DSD increase fuel mist explosion severity.